Vibration Dynamics and Control - Genta, Giancarlo; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Vibration Dynamics and Control summarizes the fundamentals of the mechanics of vibrations and provides the necessary theoretical background for the subject while also presenting real-life design applications. The material also includes problem sets for use by students and practicing design engineers. Organized for classroom use, this book is comprised of thirty concise chapters. The first part addresses the dynamics of linear, time invariant systems, including basic concepts of linear dynamics of discrete systems, an introduction to the dynamics of controlled structural systems, and analysis of the dynamic behavior of continuous system using discretization techniques. The second part focuses on the study of nonlinear and non-time invariant systems, and stresses the practical aspects of these subjects. The third part incorporates applied aspects of vibration mechanics, such as the dynamics of rotating machines and reciprocating machines. With a unified approach, consistent use of symbols and terminology, and an emphasis on practical applications, Vibration Dynamics and Control is accessible to students and in a range of mechanical, aeronautical, and mechatronic specialties. It is also suitable as a reference work for design engineers specializing in rotor dynamics, torsional vibration, modal analysis, nonlinear mechanics, and controlled systems. An Instructor's Manual with additional supporting material is available to instructors using the book as a required textbook via a link in the right-hand column.
Dynamics of Linear, Time Invariant, Systems -- Conservative Discrete Vibrating Systems -- Equations in the Time, Frequency, and Laplace Domains -- Damped Discrete Vibrating Systems -- Free Vibration of Conservative Systems -- Free Vibration of Damped Systems -- Forced Response in the Frequency Domain: Conservative Systems -- Forced Response in the Frequency Domain: Damped Systems -- Response to Nonperiodic Excitation -- Short Account of Random Vibrations -- Reduction of the Number of Degrees of Freedom -- Controlled Linear Systems -- Vibration of Beams -- General Continuous Linear Systems -- Discretization of Continuous Systems -- The Finite Element Method -- Dynamics of Multibody Systems -- Vibrating Systems in a Moving Reference Frame -- Dynamics of Nonlinear and time Variant Systems -- Free Motion of Conservative Nonlinear Systems -- Forced Response of Conservative Nonlinear Systems -- Free Motion of Damped Nonlinear Systems -- Forced Response of Damped Nonlinear Systems -- Time Variant and Autoparametric Systems -- Dynamics of Rotating and Reciprocating Machinery -- Elementary Rotordynamics: The Jeffcott Rotor -- Dynamics of Multi-Degrees-of-Freedom Rotors -- Nonisotropic Rotating Machines -- Nonlinear Rotors -- Dynamic Problems of Rotating Machines -- Rotor Balancing -- Torsional Vibration of Crankshafts -- Vibration Control in Reciprocating Machines.
Keywords: ENGINEERING; VIBRATION; MECHANICAL ENGINEERING; ENGINEERING; VIBRATION, DYNAMICAL SYSTEMS, CONTROL; MECHANICAL ENGINEERING